Smart City Development Projections through Implementation of City Spatial Planning Policies in Building The City of Solo - Luky Tri Sasongko; Arsya Yulhandi; Azizah Alvisahrin; Riza Restianti; Wahyu Cahya Ningrum (Universitas Muhammadiyah Surakarta, 2024)
Development is part of the realization of general welfare to organize national life. The development of smart cities in Indonesia has attracted attention since the beginning of the new order until now. Therefore, the Indonesian government remains committed to overcoming the complexities of housing development by developing progressive policies that prioritize inclusiveness, poverty and poverty. In Indonesia, urban development can be achieved through urban development policies implemented by the government. From a sustainable development perspective, smart cities also address impacts on the urban environment.